Meningkatkan Aktivitas dan Kerjasama Siswa Menggunakan Model PROSPEK Pada Siswa Kelas V SDN Lokrawa - Monica Ria Rahayu; Noorhapizah (CV. ITTC INDONESIA, 2024)
The lack of student activity and cooperation ability during the learning process is a problem raised in this study. The use of the PROSPEK model is an effort to overcome these problems. Using classroom action research (PTK), this research was conducted for four meetings. The data collected is qualitative, which is collected through observing student activities and students' cooperation skills. Meanwhile, quantitative data is in the form of written test results at the time of evaluation. Based on the results of the study, teacher activity increased from a score of 25 to 31 with a